Tails of the unexpected: what really happens when dogs visit schools? - Helen Lewis (The Second AnnualINTERNATIONAL ANIMAL ASSISTED PLAY THERAPY® ONLINE CONFERENCE 2022, 2022)
As many are aware, there is growing interest in the potential benefits of dogs working with pupils in primary, secondary, and special schools throughout the UK and beyond. Dogs have also worked increasingly with school counsellors and social workers in play-based interventions to augment motivation and learning.To explore what is happening when dogs visit classrooms, we were awarded a British Academy / Leverhulme Small Research Grant award to fund a research project. As part of the project, we distributed an online questionnaire to educational professionals around the world. We received over 600 responses, and interim analysis indicates that dogs are present in classrooms around the globe, although most of our responses came from the UK and USA.Research findings illustrate a variety of ways in which dogs can support learners, and teachers have noted the benefits of animals involved in play counselling, therapy, and other play- based forms of learning. Most teachers felt that the involvement of dogs was positive for learners, however many identified some practical concerns and unpredicted realities of managing an environment where children and dogs were present. What was also not so consistent was the way that teachers reported their planning and preparation to support the reciprocal wellbeing of the dogs themselves.In this presentation we explore some of the realities of ‘incidents’ which have occurredwhile the dog was in the classroom, whether from the dog, or ‘to’ the dog and how teachers, children and dogs responded. We aim to present a balanced tale of the realities of dogs in schools with a view to considering what is best practice for all partners. This presentation will highlight the reality of including a sentient, feeling animal within the curriculum and the necessity for understanding, training, consideration, and advocacy for all concerned. The theoretical basis of this research is described and results helped define best practices in the field of Animal Assisted Play Therapy® in school settings.